Evaluating ‘Bioethical Approaches’ to Human Rights - Cochrane, Alasdair (Ethical theory and moral practice, 2012)
In recent years there has been growing scholarly interest in the relationship between bioethics and human rights. The majority of this work has proposed that the normative and institutional frameworks of human rights can usefully be employed to address those bioethical controversies that have a global reach: in particular, to the genetic modification of human beings, and to the issue of access to healthcare. In response, a number of critics have urged for a degree of caution about applying human rights to such controversies. In particular, they have claimed that human rights have unresolved distributive and foundational problems. Interestingly, however, some of these critics have gone on to suggest that it might be possible to draw on certain bioethical insights to remedy these problems with human rights. This paper evaluates these recent attempts to apply insights from bioethics to the theory and practice of human rights. It argues that while these insights do not constitute an entirely new and original contribution to human rights thinking, they do force human rights scholars and campaigners to reflect on some key issues. First of all, they force us to question the prevalent idea that human rights are always ‘inviolable trumps’. Secondly, they demand that we pay close attention to the ‘fairness’ of the institutions we charge with determining our concrete rights. And finally, and perhaps most radically, these insights challenge the notion that human rights are held exclusively by members of the human species.